Do the benefits of exercise in indoor and outdoor environments during the COVID-19 pandemic outweigh the risks of infection? - Dominski, F. H.; Brandt, R. (Sport Sciences for Health, 2020)
Therefore, the guidance based on research and official guidelines is to avoid exercise in indoor environments with higher occupancy, and if performing outdoor exer-cise (walking, running, or cycling), there is a need to keep larger social distances or adopt a side-by-side arrangement. In summary, the benefits of exercise during the COVID-19 pandemic may outweigh the risks of infection; however, caution is needed in both indoor—where con-tamination could be airborne and through touching poten-tially contaminated materials—and outdoor environments. Exercise should be as promoted as social isolation [5]. We strongly recommended that people stay active with regular exercise.The present analysis promotes a critical appraisal that is relevant to help people to stay active while preventing the spread of the disease, thus avoiding additional cases of infection in the near future by individuals who are exer-cising to maintain health but could be at risk of infection, which is a contrast to the fact that individuals exercise for better health. The summary of guidelines and orientations related to social distancing, safety and hygiene applied to exercise environments, based on research and official institutions, has useful practical applications and may col-laborate with the implementation of public health strate-gies both during the pandemic and in the post-pandemic period. Correction - https://link.springer.com/article/10.1007/s11332-020-00686-8